1997
DOI: 10.1021/ja963475s
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reduction of cis-Dimethyldiazene by the [MoFe3S4]3+ Clusters. The Four-Electron Reduction of a NN Bond by a Nitrogenase-Relevant Cluster and Implications for the Function of Nitrogenase

Abstract: The catalytic reduction of cis-dimethyldiazene by the (Et4N)2[(Cl4-cat)(CH3CN)MoFe3S4Cl3] cluster (Cl4-cat = tetrachlorocatecholate) is reported. Unlike the reduction of cis-dimethyldiazene by the Fe/Mo/S center of nitrogenase, which yields methylamine, ammonia, and methane (the latter from the reduction of the C−N bond), the reduction of cis-dimethyldiazene by the synthetic cluster yields exclusively methylamine. In separate experiments, it was shown that the C−N bond of methylamine is not reduced by the [MoF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 27 publications
(27 reference statements)
0
39
0
Order By: Relevance
“…The data as originally published and cast as a FeMoco(sr) dodecamer, i.e., as for [FeMoco(sr)] 12 , are shown in Fig. 7 along with the dodecamer model ®t to the data.…”
Section: Titration Of Femoco(sr) With Benzenethiolmentioning
confidence: 99%
See 1 more Smart Citation
“…The data as originally published and cast as a FeMoco(sr) dodecamer, i.e., as for [FeMoco(sr)] 12 , are shown in Fig. 7 along with the dodecamer model ®t to the data.…”
Section: Titration Of Femoco(sr) With Benzenethiolmentioning
confidence: 99%
“…Ever since the iron-molybdenum cofactor (FeMoco) of Azotobacter vinelandii and Klebsiella pneumoniae nitrogenase was isolated [1], interest in the chemistry [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16], electronic structure [17,18,19,20,21,22,23,24,25], and rational synthesis [26,27,28,29,30,31,32,33,34] of this heterometal cluster has been intense. After publication of the solution to the crystal structure of the nitrogenase enzyme [35,36], this interest became structurally more explicit [13,37,38,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…While a FeMo-cofactor bound diazene seems likely as an early intermediate in the pathway, assessment of the interactions of diazene with nitrogenase have proven challenging because of the short half-life of diazene in aqueous solutions. McKenna and coworkers (29,30) were able to demonstrate that dimethyldiazene (H 3 C-N=N-CH 3 ) and diazirine (cyclic methyldiazene) are substrates for nitrogenase. More recently it was shown that methyldiazene (HN=N-CH 3 ) could be used as a substrate for nitrogenase (27).…”
mentioning
confidence: 99%
“…4-5-6, 2008 Crvstallographic and Structural Analysis Of Iron Helerometallic Compounds There are in total only three compounds [150,199,342] distortion being examples of distortion isomerism. [32] There are, however, several cases where there are crystallographically different moieties in a unit cell [9,11,15,30,31,39,50,53,56,71,72,106,124,151,173,190,198,210,235,245,248,261,267,274,288,299,300,317,340,342]. There are even three crystallographically independent units in {(CO) 9 Fe 2 Ru 2^4 -CHC(CH 2 )CHCCH 2 ]cp 2 } .…”
Section: Cluster Type Femm'm"mentioning
confidence: 99%
“…Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/8/15 3:37 AM of (r| 6 -l,3,5-tris((r| 5 -cyclopentadienyl)-dicarbonyliron)benzene)-tricarbonylchromium) [45] There are in total 23 generally black compounds containing an Fe 3 Mo cluster [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] ( Table 2). Two of them [46] have adopted a distorted Roussin-like cuboidal structure with MoFe 3 S 3 cores.…”
mentioning
confidence: 99%